The Effect Of Giving Amino Acid Solutions Based On Maggot Bsf (Hermetia Illucians) With Different Concentrations Into The Feed On The Percentage Of Breast And Back Of Kub Chickens - Jirfan Dawanto (Jurnal Syntax Transformation, 2023)
JIRFAN DAWANTO (4517035005). The Effect of Giving Amino Acid Solutions Based on BSF Maggots (Hermetia Illucians) with Different Concentrations into the Feed on the Percentage of Breast and Back of KUB Chickens. (Under the guidance of Asmawati Mudarsep as the main guide and Muhammad Idrus as the aggota guide). KUB chickens are widely kept by farmers because they have fast growth. The current constraint on native chicken farming is the high price of feed raw materials. Therefore, Maggot from the Black Soldier Fly fly (Hermetia Illucens) is one of the best alternatives as a mixture of chicken feed because it has a nutrient composition that is almost the same as fish meal. Based on this, this study aims to determine the Effect of Giving Amino Acid Solutions Based on BSF Maggot (Hermetia Illucians) with Different Concentrations into Feed on the Percentage of Breast and Back of KUB Chickens. This study used the DOC of 96 KUB chickens and was kept for 60 days with a cage map of 16 plots and each plot consisted of 6 KUB chickens. Feed used at the age of 1-30 days is given BP-11 granules, then at the age of 31-60 days using mixed feed by adding a fermented Maggot-based amino acid solution arranged according to treatment. The treatment used is the administration of BSF maggot-based amino acid solutions , namely: P0, P1 (15 ml), P2 (30 ml), P3 (45 ml) The results of the analysis of various doses of Maggot amino acid solution as an additive to mixed feed showed results that had no real effect (P>0.05) on the percentage of breast and back of KUB chickens. However, the administration of Maggot amino acid solution as an additive to mixed feed did not reduce the weight of KUB chicken breasts and buttocks and showed good performance